Argon laser photocoagulation in a case of feto-fetal transfusion síndrome - Loza, Ernesto Molina (2013)
The first case of fetal surgery in Peru in a woman in her first 27 weeks pregnancy and diagnosis of category Quintero III feto-fetal transfusion syndrome is reported. It was performed at Hospital Nacional EsSalud Huancayo Ramiro Priale Priale using transcutaneous argon laser photocoagulation. Post operatory outcome was good and fetuses were born by cesarean section after 25 days from photocoagulation due to premature rupture of membranes.Key words: Feto-fetal transfusion syndrome, argon laser photocoagulation.